Positive Solutions for a Coupled System of Nonlinear Semipositone Fractional Boundary Value Problems - S. Nageswara Rao; M. Zico Meetei (International Journal of Differential Equations)
In this paper, we consider a four-point coupled boundary value problem for system of the nonlinear semipositone fractional differential equation D0+αu(t)+λf(t,u(t),v(t))=0,  0<t<1, D0+αv(t)+μg(t,u(t),v(t))=0,  0<t<1, u(0)=v(0)=0,  a1D0+βu(1)=b1D0+βv(ξ), a2D0+βv(1)=b2D0+βu(η),  η,ξ∈(0,1), where the coefficients ai,bi,i=1,2 are real positive constants, α∈(1,2],β∈(0,1],D0+α, D0+β are the standard Riemann-Liouville derivatives. Values of the parameters λ and μ are determined for which boundary value problem has positive solution by utilizing a fixed point theorem on cone.